FAKTOR PENGUNGKAPAN MANAJEMEN RISIKO PADA PERUSAHAAN PERTAMBANGAN DI INDONESIA - Talitha Rachel Humaira; Dinaroe Dinaroe (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This study aims to examine the effect of firm size, leverage, profitability, and board size on management risk disclosure. This research is quantitative. The research population comprises 52 mining companies listed on the IDX in 2018-2020. The sampling method used is purposive sampling to obtain 35 research samples. The research data was obtained from the company's annual report published on the Indonesia Stock Exchange's web page. Data were analyzed using multiple linear regression with SPSS version 22. The results showed that firm size, leverage, profitability, and board of commissioner's size have a significant effect on risk management disclosure simultaneously. Partially, firm size, leverage, and board of commissioner's size affect risk management disclosure, while profitability does not affect risk management disclosure.